(untitled) (International Journal of Food and Nutritional Sciences, 2022)
As we all know Helmet is essential for our daily lives. Our brain is a crucial organ where it controls our thoughts, memory and emotions. In 2020 there were nearly 159,000 deaths due to on account of motor cycle riders not wearing a helmet. Concerning total percentage of road accidents two-wheelers constituted the highest proportion of 44.5% and the age group of persons involved in those tragedies are in-between 15 to 49 years. In this regard we want to curtail this risk and we have developed a project using Machine Learning and OPEN CV tools for Helmet Detection. We also use a camera module to detect the face of a person. The dataset is a set of images which is fed to the ML model and it processes it and outputs the real time status of the person/driver is wearing a helmet or not.By using YOLO algorithm, I created a predictive model that can be able to detect persons who are riding motorcycles without helmet in any condition.